Wiley encyclopedia of composites - Borzacchiello, Assunta; Nicolais, Luigi (John Wiley & Sons, Inc., 2012)
"This Wiley Encyclopedia of Composites, Second Edition includes 265 articles on composite materials and related processing technologies, most of which are completely new to this edition. Articles address properties, processing, formulation, design, analysis, evaluation, manufacture, testing, and reliability. The entire range of industrial applications of composites is covered"-- Provided by publisher